Effect Of Recovery Time After Match On Muscle Explosive Power On Football Athletes - Adelia Handoko; Cahyo Bagaskoro (Saintika Medika, 2021)
Football is one of the most prestigious forms of sports that are in great demand by the public. Many football clubs that take part in the competition have a tight match schedule. This causes the recovery time for athletes to be short and lead to fatigue. The purpose of this study was to determine the effect of recovery time after the match on the explosive power of leg muscles in soccer athletes. This study was an experimental study with a pretest-posttest group design. The sampling method used was simple random sampling to get 40 research subjects divided into 2 groups, namely groups with recovery time of 2 days and groups with recovery time of 5 days. The assessment used is measurement of explosive limb muscle power using the vertical jump technique before and after receiving the recovery period. To test the normality of data using Shapiro-Wilk continued with the comparative data test in the form of an unpaired t test. The results of the study in groups with a recovery time of 2 days were worth -3.7cm and the group with a recovery time of 5 days was 2.9cm. These results were analyzed using unpaired t-test showing p value = 0,000 (p<0.05) which showed there were significant differences between the two groups. The conclusion of this study is that there is an effect of recovery time after the game on the leg muscle explosive power in soccer athletes. Recovery time of 5 days is better than 2 day after competition. It is very important to pay attention to recovery time in athletes, the recommendation of this study is a minimum of 5 days.